Hubungan Kepercayaan Diri Dengan Penyesuaian Diri Siswa Putra Kelas VII SMP Al Musyaffa Kendal - M. Faiq Atho’illah; Tri Suyati; Agus Setiawan (LPPM Politeknik Pratama, 2023)
The background of this research is that class VII students at SMP Al Musyaffa Kendal do not have enough self-confidence to adapt to their environment which affects their learning process at school. Based on a questionnaire about self-confidence that has been distributed it was found that only 18% of students did their assignments on time, students did not know the talents that were in me 42%, students felt inappropriate if appointed to be class leaders 54%, students had difficulty developing talents that 69% owned, and 70% embarrassed to ask. then in the self-adjustment questionnaire it was found that on the item it was difficult to start a conversation with strangers 90%, I had difficulty telling problems 66%, I thought I could not socialize properly 60%, and tended to close myself 75%. From the results of the questionnaire that has been distributed, it shows that there are problems with the self-confidence and self-adjustment of class VII students at SMP Al Musyaffa Kendal. This type of research is a quantitative research with a correlational research design. The research data population is 192 students, covering class VII A-F. The trial sample (Try out) was 29 students of class VII F. The sample in this study were 62 students who were taken by random sampling technique. The data collection tool used is a self-confidence scale and a self-adjustment scale. The results of the hypothesis test in this study used the person product moment correlation test, indicating that the person product moment correlation test of the two variables obtained a significance result of (r) = 0.455. While the value of r table for the number of samples is 62 with a significance level of 5% of 0.240, which means that the two variables have a significant relationship. Because the r count value is 0.455 > r table 0.240 when matched with the interpretation table it shows that the self-confidence variable and the adjustment planning variable have a sufficient level of relationship. From these results indicate that there is a relationship between self-confidence and self-adjustment of class VII male students at SMP AL Musyaffa Kendal.